Deep and underground excavations : proceedings of sessions of GeoShanghai 2010, June 3-5, 2010, Shanghai, China - Tonon, Fulvio; Liu, Xian, 1977-; Wu, Wei, 1961- (Geotechnical special publication, 2010)
This Geotechnical Special Publication contains 49 papers presenting the latest research into using the subsurface as a civil engineering dimension. The pressure exerted by increasing population, sensitivity toward the environment, and the ever-increasing cost of the land are a few of the reasons that underground excavations are necessary to society's health and future. Excavations below the surface provide space for services, transportation of people and goods, water supply and disposal, sanitation, and storage. These papers offer global examples of practical applications of excavations, especially in China. These papers analyze deep excavations and retaining structures, tunnels and underground excavations, and new frontiers in urban geotechnology. Proceedings of sessions of GeoShanghai 2010, held in Shanghai, China, June 3-5, 2010. --